Overexpression of DSPP promotes the proliferation and migration of astrocytes. (29th May 2021) - Gao, Huasong; Fan, Shaochen; Xie, Liqian; Hu, Shukun; Zhang, Yi
Highlights: DSPP expression was increased in reactive astrocytes comparing to normal ones. Overexpression of DSPP could promote the proliferation and migration of the cells. Overexpression of DSPP obviously increased the activation of Akt/mTOR pathway in astrocytes. Abstract: Astrocytes are activated after central nervous system (CNS) injury, such as spinal cord injury (SCI). Activated astrocytes can form glial scar to block nerve regeneration. Dentin sialophosphoprotein (DSPP), a member of the SIBLING (Small integrin-binding ligand N-linked glycoproteins) family, has been reported to contribute to the proliferation and migration of different types of tumor cells, including glioma. However, the functions of DSPP in reactive astrocytes after CNS injury remain unknown. In this study, starvation-serum stimulation model in astrocytes was conducted to explore this issue. Our results showed that DSPP expression was increased in reactive astrocytes comparing to normal ones. Meanwhile, up-regulation of DSPP was accompanied with PCNA and GFAP. To explore the role of DSPP in astrocytes, we overexpressed DSPP with recombinant GFP-DSPP plasmid and the results showed that overexpression of DSPP could promote the proliferation and migration of the cells, the important characteristics of reactive astrocytes. In addition, overexpression of DSPP obviously increased the activation of Akt/mTOR pathway in astrocytes. Taken together, we demonstrated that DSPP may play a key role in the proliferation and migration of astrocytes, suggesting that targeting DSPP might be a promising therapeutic strategy for treating CNS injury which characterized by glia scar formation.